Genetic technology in the targeted therapy of Alport Syndrome - Magdalena Kłusek; Bartosz Pawłowski; Michał Sienkiewicz; Anna Mandziuk (Quality in Sport)
Introduction and aim of the study: Alport syndrome is the most common inherited chronic kidney disease, with three distinct patterns of inheritance: X-linked, autosomal, and digenic. Currently, there is no curative treatment for Alport syndrome. This review aims to provide updated knowledge about Alport syndrome, including its clinical and genetic characteristics and therapies that slow disease progression.